ANALISIS SUMBER DAN PENGGUNAAN KAS PADA PT. TIRTA MAHAKAM RESOURCES TBK BUKUAN - Rubiyanto Pangestu; Martinus Robert Hutauruk; Pantas Pangondian Pardede (University of Widya Gama Mahakam Samarinda, 2019)
The purpose of this study was to determine whether the source of cash receipts is greater than the source of cash usage at PT. Mahakam Resources Tbk Bukuan. This study uses a descriptive method with a quantitative approach by comparing financial statements (balance sheets / statements of financial position) in 2015 compared with 2016 at PT. Mahakam Resources Tbk Bukuan. From the results of the analysis, it can be seen that the source of cash receipts at PT. Mahakam Resources Tbk Bukuan experienced a decrease in cash in 2016 amounting to Rp -338,652,449 from cash sources of Rp 99,977,724,508 and cash usage of Rp 130,170,313,317 and thus the hypothesis proposed can be accepted.